부산지역 사업장 폐수 중 총유기탄소(TOC)와 유기물 지표간 상관관계 연구 - 최성화; Seong-hwa Choi; 정미은; Mi-eunjeong; 주광용; Kwang-yong Joo; 최유정; Yoo-jeong Choi; 윤나나; Na-na Yoon; 곽진숙; Jin-suk Kwak; et al. (환경분석과 독성보건, 2020)
The introduction of total organic carbon (TOC) as a new organic matter index for industrial wastewater is under consideration. In this study, we investigated characteristics of organic pollutant indexes (TOC, BOD 5 , COD Mn , COD Cr ) for 11 industrial categories comprising 210 industrial wastewater samples from Busan, Korea. Average organic concentrations for chemical manufacturing and food manufacturing industries are higher than that for other industries. The organic matter oxidation rates of COD Cr and COD Mn for TOC are 88.7% and 51.9%, respectively. Furthermore, the COD test can be underestimated for organic compounds in wastewater. The correlation between TOC and organic matter indexes was in the order of COD Mn (r = 0.970) > COD Cr (r = 0.956) > BOD 5 (r = 0.812)(p < 0.01). In conclusion, the introduction of TOC, which has higher oxidation rate than COD and high correlation with existing organic matter indexes, is appropriate as an organic index to replace COD.